ANALISIS YURIDIS TINDAK PIDANA PENCUCIAN UANG PERSPEKTIF HUKUM INTERNASIONAL DAN HUKUM NASIONAL - Riza Ananda Putri (PT. Habe Cendekia Utama, 2025)
Public coffers, social fabric, and national economic security are all negatively impacted by money laundering offenses. The proliferation of new crimes fueled by money laundering has the potential to undermine public trust in the justice system and endanger individual liberties. Therefore, using a normatized yuridis research technique, we need to determine how far criminal policy can go in its present efforts to combat illegal money laundering. Finding out how Indonesia's criminal policy on money laundering relates to international law and how the country's legal system handles such matters is the main goal of this study. Law number 8, passed in 2010, governs the principles of national criminal law on the prevention and elimination of money laundering offenses, according to study. The following international tools illustrate the community's efforts to combat the worldwide menace of money laundering. The United Nations convention on transnational crimes provided the groundwork for the development of this body of law. When it comes to developing unobstructed criminal processes of money plain in Indonesia, the criminal policy competency of the legal system has failed in the financial monitoring system, which is a severe countermeasure.